Governance reform under real-world conditions citizens, stakeholders, and voice - Odugbemi, Sina; Jacobson, Thomas L. 1952- (World Bank, 2008)
"Governance Reform under Real-World Conditions: Citizens, Stakeholders, and Voice is a contribution to efforts to improve governance systems around the world, particularly in developing countries. The contributors, who are academics and development practitioners, provide a range of theoretical frameworks and innovative approaches and techniques for dealing with the most important nontechnical or adaptive challenges that impede the success and sustainability of reform efforts." "The editors and contributors hope that this book will be a useful guide for governments, think tanks, civil society organizations, and development agencies working to improvethe ways in which governance reforms are implemented around the world."--BOOK JACKET